2020
DOI: 10.1002/npr2.12096
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the influence of cedar fragrance on cognitive function and behavioral and psychological symptoms of dementia in Alzheimer type dementia

Abstract: We examined whether symptoms of dementia are improved by olfactory nerve stimulation in Alzheimer type dementia patients. First, a stick‐type olfactory identification ability test was performed in patients with Alzheimer type dementia, to select patients without olfactory dysfunctions. Then, these patients were randomly assigned into the intervention (n = 19) and the control groups (n = 17). To evaluate the effects of olfactory nerve stimulation, we exposed the intervention group to a disinfecting ethanol with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…Improvements in responsive behaviours such as agitation, anxiety and irritability were also reported by Takahashi et al (2020) in the experimental group after environmental exposure to an ethanol cleaning solution with added cedar fragrance and distilled solution with cedar sprayed on clothing and bedding, compared to the control group who were exposed to the ethanol solution without fragrance. Sakamoto et al (2012) found a significant decrease in the Cohen-Mansfield Agitation Inventory (CMAI) (Cohen-Mansfield & Kerin, 1986) score following a 12-month period of olfactory stimulation using a patch worn by residents in nursing homes.…”
Section: Responsive Behavioursmentioning
confidence: 73%
See 3 more Smart Citations
“…Improvements in responsive behaviours such as agitation, anxiety and irritability were also reported by Takahashi et al (2020) in the experimental group after environmental exposure to an ethanol cleaning solution with added cedar fragrance and distilled solution with cedar sprayed on clothing and bedding, compared to the control group who were exposed to the ethanol solution without fragrance. Sakamoto et al (2012) found a significant decrease in the Cohen-Mansfield Agitation Inventory (CMAI) (Cohen-Mansfield & Kerin, 1986) score following a 12-month period of olfactory stimulation using a patch worn by residents in nursing homes.…”
Section: Responsive Behavioursmentioning
confidence: 73%
“…Among the 20 studies, eight used a control group composed of older people of similar age to those with dementia ( n = 5) (El Haj et al, 2018; Glachet et al, 2019; Glachet & El Haj, 2019, 2020a, 2020b), people with dementia with the same demographic characteristics to the experimental group ( n = 2) (Sakamoto et al, 2012; Takahashi et al, 2020) and older and young people ( n = 1) (Lopis et al, 2021). Jimbo et al (2009) and Takahashi et al (2020) included care staff and caregivers in their sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, OI dysfunction occurs in many neuropsychiatric diseases, including frontotemporal dementia ( 20 ), schizophrenia ( 21 ), bipolar disorders ( 22 ), autism spectrum disorder ( 23 ). Furthermore, behavioral and psychological symptoms in AD, such as agitation, anxiety, and irritability ( 24 ), would change upon exposure to fragrance ( 25 ).…”
Section: Introductionmentioning
confidence: 99%